Systemic lupus erythematosus and thyrotoxicosis: a hitherto little recognised association. Issue 5 (May 1989) - Rodrigué, S; Laborde, H; Catoggio, P M
Abstract : Six patients are reported in whom systemic lupus erythematosus (SLE) and thyrotoxicosis coexisted. All had four or more American Rheumatism Association criteria (1982) for the diagnosis of SLE and had clinical manifestations and function test results characteristic of hyperthyroidism (except for one who had been thyroidectomised previously). In three patients the diagnosis of hyperthyroidism preceded that of SLE, in two patients both diseases began simultaneously, and only in one was the diagnosis of thyrotoxicosis made after that of SLE. It is suggested that hyperthyroidism associated with SLE may be a form of presentation of thyroiditis. This association may pass unnoticed because of the similarity of some clinical manifestations.